Money growth and consumer price inflation in the euro area: An update - Martin Mandler; Michael Scharnagl (Deutsche Bundesbank, 2023)
We update the wavelet-based analysis of the relationship between money growth and inflation in the euro area in Mandler and Scharnagl (2014). The relationship between headline M3 growth and inflation at low frequencies has weakened over the 1990s. However, we find evidence of stable comovement between money growth adjusted by real GDP growth and consumer price inflation for cycles of 24 years and longer duration. The long-run fluctuations of adjusted money growth and inflation move roughly about 1:1 and are contemporaneous, i.e. there is no lead of money growth. Our analysis of cycles in both variables of 24 years and longer provides information on the relationship between the variables from the late 1980s to the early 2000s.
Keywords: C30; E31; E40; 330; money growth; inflation; euro area; wavelet analysis